Mechanism of Exosomes Involved in Osteoimmunity Promoting Osseointegration Around Titanium Implants With Small-Scale Topography - Zhang, Ting; Jiang, Mengyang; Yin, Xiaojie; Yao, Peng; Sun, Huiqiang (Frontiers in Bioengineering and Biotechnology, 2021)
Exosomes are nanoscale extracellular vesicles. Several studies have shown that exosomes participate in intercellular communication and play a key role in osseointegration. However, it is unclear whether exosomes and their contents participate in the communication between the immune and skeletal systems in the process of osseointegration. In this study, we obtained smooth titanium disks by polishing and small-scale topography titanium disks by sandblasted large-grit acid-etched (SLA) technology combined with alkali thermal reaction. After stimulating mouse RAW264.7 cells with these two kinds of titanium disks, we co-cultured the MC3T3-E1 cells and the RAW264.7 cells, obtained and identified the exosomes derived from RAW264.7 cells, and studied the effect of the osteoimmune microenvironment and the exosomes on the osseointegration of mouse MC3T3-E1 cells. Cell counting kit-8 (CCK-8), real time quantitative PCR, western blotting, alizarin red staining, and quantitative and confocal fluorescence microscopy were used to study the effects of exosomes on MC3T3-E1 cells; RNA sequencing and correlation analysis were performed. We found that the osteoimmune microenvironment could promote the osseointegration of MC3T3-E1 cells. We successfully isolated exosomes and found that RAW264.7 cell-derived exosomes can promote osteogenic differentiation and mineralization of MC3T3-E1 cells. Through RNA sequencing and gene analysis, we found differentially expressed microRNAs that targeted the signal pathways that may be related, such as mTOR, AMPK, Wnt, etc, and thus provide a reference for the mechanism of osteoimmunue regulation of implant osseointegration. The study further elucidated the mechanism of implant osseointegration and provided new insights into the effect of exosomes on implant osseointegration, and provided reference for clinical improvement of implant osseointegration and implant success rate.